2008
DOI: 10.1007/s10295-008-0460-4
|View full text |Cite
|
Sign up to set email alerts
|

Mannosylerythritol lipids: a review

Abstract: Mannosylerythritol lipids (MELs) are surface active compounds that belong to the glycolipid class of biosurfactants (BSs). MELs are produced by Pseudozyma sp. as a major component while Ustilago sp. produces them as a minor component. Although MELs have been known for over five decades, they recently regained attention due to their environmental compatibility, mild production conditions, structural diversity, self-assembling properties and versatile biochemical functions. In this review, the MEL producing micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
102
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(114 citation statements)
references
References 72 publications
(171 reference statements)
1
102
0
3
Order By: Relevance
“…In agreement with other reports, the preference of these two glycolipids is affected considerably by the nitrogen source [1] [37]. Additionally, in this study we showed first that UA is the main glycolipid when esterified fatty acids are accumulated in the lipid bodies, and second, that U. maydis is an important cell factory that produces not only glycolipids, but also fatty acids which may have potential application in biofuels.…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with other reports, the preference of these two glycolipids is affected considerably by the nitrogen source [1] [37]. Additionally, in this study we showed first that UA is the main glycolipid when esterified fatty acids are accumulated in the lipid bodies, and second, that U. maydis is an important cell factory that produces not only glycolipids, but also fatty acids which may have potential application in biofuels.…”
Section: Discussionsupporting
confidence: 92%
“…pharmazeutischen Bereich interessant machen. Dazu zählen u. a. antibiotische und cancerostatische Anwendungen [5,6]. Für die industrielle Herstellung dieser Biotenside sind jedoch noch Verbesserungen der Ausbeute und anwendungsspezifischen Tensideigenschaften notwendig.…”
Section: Problemstellungunclassified
“…They include surfactin and iturin produced by B. subtilis strains (Ahimou et al, 2000), rhamnolipids from Pseudomonas species (Abalos et al, 2001), and biosurfactants produced by some fungi (Arutchelvi et al, 2008). However, there are few reports about the antimicrobial activity of biosurfactants isolated from Staphylococcus.…”
Section: Resultsmentioning
confidence: 99%